Effect of lime application on phosphorus adsorption and desorption in post-active acid sulfate soil, Thailand - Sukyankij, Saychol; Sukyankij, Sopida; Khongsud, Chalinee; Panich-pat, Thanawan (Brawijaya University, 2024)
The application of lime is the general method of improving acid sulfate soils. However, if a lot of lime is applied, it can reduce the bioavailability of nutrients in the soil, especially phosphorus. The objective of this study was to investigate the effects of liming at different rates on the availability, adsorption, and desorption of phosphorus in two post-active acid sulfate soils (Ay and Se). The experiment was performed in the laboratory. The experiment was laid out in a completely randomized design (CRD) with four treatments and three replicates, i.e., the application of lime at a rate of 0 (control), 0.5, 1.0, and 2.0 times the lime requirement (LR). The lime requirements of the soils in the Ay and Se were 5,690 and 12,250 kg CaCO3/ha, respectively. The finding revealed that increasing the amount of lime could increase soil pH, available phosphorus, and the phosphorus activation coefficient. Application of lime at a dosage of 1.0-2.0 LR resulted in the highest phosphorus adsorption maximum (Qm) (380 mg/kg), while 0.5 LR resulted in the lowest Qm (353 mg/kg) in Se soil only. As lime dosage increased, phosphorus desorption maximum (Dm) and phosphorus desorption ratio (Dr) increased, with 2.0 LR yielding the highest values (124 mg/kg and 23.6 percent for Ay soil, and 77.3 mg/kg and 20.3 percent for Se soil, respectively). The results suggested that applying lime according to the lime requirement test, especially 2.0 LR, is the best option to promote the release of phosphorus in post-active acid sulfate soils.